SBS - Malay's Desserts / Ahmad Nabil Najmi Rosnan and Muhammad Nur Iman Md Sabasari - Rosnan, Ahmad Nabil Najmi; Md Sabasari, Muhammad Nur Iman (2022)
Our business is named SBS - Malay's Desserts. It is based in Seri Manjung, Perak. It is located in W311 Fasa 3A, Seri Manjung, 32040, Sitiawan, Perak, Malaysia. This Business is organizes by two people which is Muhammad Iman who is responsible in operation and logistic while Ahmad Nabil responsible in marketing. It is a home-based business. This business solely operates at home and doing delivery to nearby residential. Our mission is to provide food that are premium quality but at an affordable price, to ease the mothers to prepare breakfast and evening meal, and to help community by providing food at low price so that they can resell and get some income. While the vision of our business is to become one of the main suppliers providing Malay's Dessert food in Perak. We offered 3 main desserts for our customer to choose which consist of karipap, cucur badak, and talam. There are two version of food provided which is frozen and cooked for karipap and cucur badak. While for talam we only provided a cooked version. For karipap and talam, we offer two variation that customer can choose from which is kentang and sardin for karipap, and talam keladi and talam tokyo for talam. For marketing purposes, we have chosen an online platform from Facebook to advertise our product. This is one of the alternatives we use to communicate with our customer as well as to promote our product. It is also being used to give some tips regarding the dessert that we sell and to share latest information about our business. The customer can order directly by clicking the WhatsApp link through our Facebook page or directly message at our Facebook page.